Alexander Pope’s Dunciad and Ned Ward’s London Spy: Experiments in Text Visualization - Muri, Allison (Lumen)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 2022)
Text visualization is the technique of using graphs and charts to examine text as data. Often, these do not represent a text directly and instead display an output based on word counts, word sequences, and so on. This technique can provide insights into important keywords in a text, provide an overview of textual content, or reveal trends and patterns within one text or across many texts. This paper describes recent development of and experiments with several tools for the Grub Street Project to generate visualizations of eighteenth-century texts, especially in terms of the spatial relationships of words and entities on the pages of the original documents. Two examples are discussed in this article as test cases: Edward Ward’s The London Spy Compleat, in Eighteen Parts (1703) and Alexander Pope’s The Dunciad. With Notes Variorum (1729).